2007
DOI: 10.1128/aem.02388-06
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Cohesiveness Measurement Using a Novel Atomic Force Microscopy Methodology

Abstract: Biofilms can be undesirable, as in those covering medical implants, and beneficial, such as when they are used for waste treatment. Because cohesive strength is a primary factor affecting the balance between growth and detachment, its quantification is essential in understanding, predicting, and modeling biofilm development. In this study, we developed a novel atomic force microscopy (AFM) method for reproducibly measuring, in situ, the cohesive energy levels of moist 1-day biofilms. The biofilm was grown from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 45 publications
2
71
0
1
Order By: Relevance
“…In one abrasion study of mixed culture biofilms from activated sludge, AFM was 81 successfully implemented to describe the increasing cohesiveness of the sample with increasing 82 sample depth under elevated shear loading (Ahimou et al 2007 …”
mentioning
confidence: 99%
“…In one abrasion study of mixed culture biofilms from activated sludge, AFM was 81 successfully implemented to describe the increasing cohesiveness of the sample with increasing 82 sample depth under elevated shear loading (Ahimou et al 2007 …”
mentioning
confidence: 99%
“…The wet mode experiments in M63 solution preserves the biofilm interactions and attachment and provides accurate force measurements compared to dry mode [23]. A minimum of 10 force measurements were collected on each of five different biofilm regions on the same sample, each region covering an area of 100 µm × 100 µm, affording a typical total of >100 force measurements.…”
Section: Biofilm Analysis: Afm and Force Analysismentioning
confidence: 99%
“…Karunakaran et al (2010), for example, suggested that attractive electrostatic forces between charged proteins in EPS could impart cohesive stability to the biofilm matrix. Similarly, Ahimou et al (2007b) found that the calcium absorption of biofilms has a considerable effect on the cohesive energy of the EPS matrix, which may be attributed to the anionic properties of protein. Some scholars have even shown that the predominance of protein compositions rather than polysaccharides leads to greater biofilm stability (Sheng et al 2010).…”
Section: Definition Characteristics and Spatial Distribution Of Epsmentioning
confidence: 99%
“…Meanwhile, AFM topographic images also reveal the nature of adsorbed EPS. Ahimou et al (2007b) employed AFM to measure in-situ EPS/EPS and cell/EPS interactions within a well-defined volume of biofilm. The in-situ measurement of the cohesive energy levels of moist biofilms revealed a stronger effect of calcium absorption on the cohesive energy of the EPS matrix and a weaker effect of calcium absorption near the microbial cell surface.…”
Section: Atomic Force Microscopymentioning
confidence: 99%